Class-D Audio Amplifier using Sigma-Delta (ΣΔ) Modulator - Nour El Imane Bellili; Khaled Bekhouche (IAES Indonesian Section, 2022)
Pulse width modulation and pulse density modulation are deemed to be main modulation techniques, even PDM could not emulate PWM, in terms of, basically, simplicity. PDM bitstream is encoded through sigma-delta modulation. Since sigma-delta modulation, compared to PWM, needs very high switching frequency and more complicated materials to compose circuits, it’s more difficult to design one. In this article we design a low-power class-D audio amplifier circuit where the analog signal is encoded into pulse density modulation (PDM) using a first-order sigma-delta (ΣΔ) modulator. The designed circuit is built using Orcad-PSpice and results are analyzed with Matlab. A second-order integrator, a voltage divider as a feedback loop are used to mitigate basically, THD and get high efficiency. The audio signal is passed to the EM speaker through a Butterworth low-pass filter. A low THD of less than 0.2 % is obtained comparing to similar circuits in the literature and a high efficiency of 92 % is achieved.